2020
DOI: 10.4236/ojmn.2020.102020
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopic Third Ventriculostomy versus Ventriculo-Peritoneal Shunt for Infant Hydrocephalus

Abstract: Introduction: Patients with hydrocephalus, which is the most pediatric neurological disorder, undergo Cerebrospinal fluid (CSF) diversion through third ventriculostomy or ventriculo-peritoneal shunt. Up to date, the optimal hydrocephalus treatment modality is not clear. Aim: We compared the outcome of endoscopic third ventriculostomy (ETV) versus ventriculo-peritoneal shunt (VP shunt) as a second surgical intervention in management of Infant hydrocephalus concerning success rate and complications. Patients and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Some authors described ETV failure as the shunt placement requirement. According to Kadrian et al, there is a strong effect of patient age on outcome [ 21 ]. They recorded extremely low reliability of ETV in infants younger than 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors described ETV failure as the shunt placement requirement. According to Kadrian et al, there is a strong effect of patient age on outcome [ 21 ]. They recorded extremely low reliability of ETV in infants younger than 1 month.…”
Section: Discussionmentioning
confidence: 99%
“…However, another meta-analysis demonstrated that, ETV had lower overall complication rate, infection, and revision surgery, shorter operative time and hospital stay duration but were comparable as regard to rate of symptom improvement, hematoma, and mortality when compared to VP shunt [18] . Finally, Abdel-Aziz et al [19] concluded that, ETV is superior than VPS as it is associated with lower rate of postoperative infection, shorter duration of operation. But they could not discover statistical difference regard PO obstruction, need for revision surgery or overall survival.…”
Section: Disucssionmentioning
confidence: 99%